COMPETENCE AND MOTIVATION ANALYSIS OF EMPLOYEE PERFORMANCE IN THE ECONOMIC SECTION OF LAMPUNG CENTRAL DISTRICT - Rafian Joni; Epi Parela (Saburai International Journal of Social Sciences and Development, 2022)
Organizations must adapt to existing changes in order to survive and thrive. Existing conditions in the Economic Section of Central Lampung Regency, among others, low employee performance, this can be seen from the presence of employees who have not shown their responsibilities in completing work and procrastinating work. This research is quantitative in nature where the explanation is objective by explaining the existing approaches. This study used 21 research respondents. There are three variables in this study, namely: 2 (two) independent variables (X1 and X2) and 1 (one) dependent variable where Competence (X1) and Motivation (X2) are independent variables and Employee Performance (Y) is the dependent variable.From the results of data processing, it has been found that the answers to the hypothesis are as follows; There is an influence of Competence (X1) on Employee Performance (Y), with a level of influence (R-square) of 17,6 %. There is an influence of Motivation (X2) on employee performance (Y), with a level of influence of 30,7 %. There is an influence between Competence (X1), and Motivation (X2) together on Employee Performance (Y), with an influence level of 37,4 %.